فنقلات النساء في بلاغات النساء مقاربة حجاجية (Journal of the College of Basic Education, 2025)
Arabic culture, in its literary form, was not far from the social reality that people lived in those times, but rather it showed many representations that revealed something of that bygone eraPerhaps the book (Women’s Statements) represents this phenomenon based at the heart of the texts that revealed what Arab women - Muslims and others - possess in terms of high culture and a solid conversational style that contains many suggestive connotations. Based on the formation of these dialogues on the basis of (translation) of issuing a statement and giving a response to it, the aim of the research became to examine these verbal utterances and clarify their rhetorical and communicative value according to the theory of rhetorical argumentation.